The 3-3-1 Models in Current Particle Physics - Dong, Phung Van (Communications in Physics, 2014)
We review the main contribution of the Division for Theoretical Particle Physics at the Institute of Physics, VAST in building the models based on \(SU(3)_CSU(3)_L U(1)_X\) gauge unification.